2020
DOI: 10.1016/j.joca.2020.02.836
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the relationship between chronic pain and cortisol levels in subjects with osteoarthritis: results from a systematic review of the literature

Abstract: Objective: Several reports in the literature have identified an association between cortisol levels and the presence of chronic pain in conditions such as rheumatoid arthritis, low back pain or whiplash. In contrast, few have examined the association of cortisol and pain in people with osteoarthritis (OA). The purpose of this systematic review was to verify the association between cortisol and pain in the OA population. Design: The databases MEDLINE, CINAHL, EMBASE were searched systematically for human studie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 49 publications
0
16
0
Order By: Relevance
“…In fact, several studies have confirmed the involvement of inflammation, neurotransmitters, the hypothalamic-pituitary adrenal axis, and cortisol levels in the biological mechanisms of OA and depression. 59–62 …”
Section: Potential Mechanisms Of Oa and Comorbid Depressionmentioning
confidence: 99%
“…In fact, several studies have confirmed the involvement of inflammation, neurotransmitters, the hypothalamic-pituitary adrenal axis, and cortisol levels in the biological mechanisms of OA and depression. 59–62 …”
Section: Potential Mechanisms Of Oa and Comorbid Depressionmentioning
confidence: 99%
“…Quick physical exercises can also elevate feelings of vitality, build team spirit, and improve mental and physical functions ( Andersen et al., 2022 ). Improper lifting techniques cause repeated strain within our bodies and when combined with overuse of specific motions and faulty postures, we are more susceptible to microtraumas that need to be addressed ( Villafañe et al., 2020 ). Gentle stretching or yoga can benefit improved blood and lymphatic flow, develop body awareness, muscular strength, and flexibility ( Mandal et al., 2021 ; Narahari et al., 2021 ).…”
Section: Nurse: Five Brief Self-care Micropracticesmentioning
confidence: 99%
“…Performing blood tests on patients undergoing total joint replacement may lead to early identification of the development of complications, such as infection, systemic inflammatory response syndrome, and deep vein thrombosis. 6 In patients undergoing TKR, changes in white blood cell count can be the consequence of leukocytosis, monocytosis, lymphocytopenia, and granulocytosis. 7,8 A variation in the platelet count can reflect changes in primary hemostasis and in the development of blood clotting; moreover, a rise in the platelet count can be a sign of hypercoagulability and a marker of infection.…”
mentioning
confidence: 99%